Highly sensitive curvature sensor based on asymmetrical twin core fiber and multimode fiber. (1st July 2017) - Wu, Yue; Pei, Li; Jin, Wenxing; Jiang, Youchao; Yang, Yuguang; Shen, Ya; Jian, Shuisheng
Abstract: A highly sensitive curvature sensor based on asymmetrical twin core fiber (TCF) and multimode fiber (MMF) is proposed and experimentally demonstrated. By applying the coupled-mode theory and equivalent refractive index model, we theoretically analyze the uncoupled feature of the TCF and the relationship between peak wavelength and the curvature. Two segments of MMF used as beam splitter and combiner are embedded on the two ends of the TCF, and the extinction ratio of the comb transmission spectrum is about 15 dB. The experimental result shows that the curvature sensitivity of the sensor can be achieved as high as 103.35 nm/m −1 ranging from 0.24 m −1 to 0.6 m −1, and the strain sensitivity is up to −4.01 pm/με in the range from 0 μ ε to 1400 με. The simultaneous detection of the curvature and strain can be realized. The temperature sensitivity is 0.431 nm/°C in the range from 40 °C to 70 °C. This fiber sensor exhibits the advantages of low cost, easy and repeated fabrication, and high sensitivity. Abstract : Highlights: The optical fiber sensor is based on asymmetrical TCF and MMF. The MMF is employed to achieve the beam splitting and combining. The sensitivity of curvature and strain is 103.35 nm/m −1 and −4.01 pm/με. The simultaneous detection of the curvature and strain can be realized.